The Indicators of Nurse's Perspective in Health Management System and Hospital Safety in Gombong Region Hospitals, Indonesia - Wulan Rahmadhani; Nur Azis Rohmansyah; Than Kyaw Soe; Jipri Suyanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2021)
Health management systems played a crucial role in hazard reduction and prevention as well as in improving employee performance. The importance of a hospital health and safety management system and there has been no study in Indonesia with the same objective based on the OSHA indicator. The purpose of this study is to evaluate the performance indicators of Hospital Safety and health management systems in hospitals in the Gombong region, Indonesia, in terms of a nurse perspective. The research method used was descriptive-analytic. The sample size consisted of 450 nurses. The questionnaire used a standard questionnaire from hospital safety and health management systems which consisted of 53 questions including 6 domains; Leadership management, Hazard identification, employee participation, Hazard prevention, evaluation and improvement program, and Education and training. Using the 1-4 Likert scale of strongly disagree, disagree, agree, and strongly agree. The highest score was 4 and the lowest score is 1. Data analysis used SPPS, t-test, and analysis of variance (ANOVA) with a significant value <0.05. Based on the research results, poor conditions occurred in several domains except in the domain of employee participation. There were significant variables between hazard identification and gender, hazard prevention and improvement program and evaluation also. Conclusion of this study, hospital administrations need to be improved and pay more attention to occupational safety and health in the workplace. To get rid of weaknesses and a mistake, we need to continuous improvement and effective evaluation of staff in training programs.